Comparing grammar of insular languages The phenomenon of parsing is a model (Journal of the College of Basic Education, 2022)
The languages ​​of the multiplicity of the multiplicity of tongues and differences manifest themselves in the races, colors and complexions; was for all mankind language communicates it with the person who is linked by ties of kinship, and the bonds of the neighborhood, and the existence of the human species multiple in their own pay languages ​​scientists to be divided along religious and natural foundations, and this division Find us linguistic factions back have different languages ​​spoken by the human races.The lesson of language up to higher stages of maturity and pays off when the student to learn on the language, and its inception, and their habitat, speakers, and their habits, and their culture, and their religion, and traditions; so it was a student of any of the languages ​​that knows its origins, and mastered all aspects, compares between them and the brothers in the linguistic species to which it belongs, to assess the linguistic judgments on scientific grounds does not accept the probability and frequency, and for this we see that the Orientalists have advanced in their studies of the Arab; because they do not teach alone, but in the context of linguistic species to which it belongs